The Effectiveness of the Work of the Poverty Reduction Coordination Team in Preparing the Regional Poverty Reduction Plan in South Sulawesi - Asmarianti, Asmarianti; Sabrina, Jeelan (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
Poverty in Indonesia is still a major problem in national development. Therefore, the Government of Indonesia has developed a top priority program, namely policies to encourage poverty alleviation that must be implemented by various regions in Indonesia. The South Sulawesi Provincial Government has established a poverty alleviation policy and formed a poverty alleviation coordinating team (TKPK). This shows the level of commitment of the South Sulawesi provincial government in achieving its target of reducing poverty. The purpose of this research is to describe and analyze the work effectiveness of the poverty alleviation coordinating team (TKPK) in developing regional poverty alleviation plans in the province of South Sulawesi. The research approach used in this study is a qualitative approach. The location of this research is at the Bapplitbangda office in South Sulawesi Province. The subjects of this study were selected through a purposive sampling technique. Data and information were obtained through in-depth interviews with the South Sulawesi provincial poverty reduction coordinating team. This study found that the effectiveness of the work of the poverty alleviation coordination team in preparing the regional poverty alleviation planning documents in South Sulawesi Province had not run optimally due to several problems, including: the high workload assigned to the team, the structural managerial function in the Poverty Reduction Coordinating Team was not optimal so the document has not been completed, and there is slow coordination between the Poverty Reduction Coordinating Team and Regional Apparatus Organizations.